Geometric shapes effect of in-duct perforated orifices on aeroacoustics damping performances at low Helmholtz and Strouhal number - Zhao, Dan (2019)
In this work, experimental studies are conducted to measure the aeroacoustics damping performances of 11 in-duct perforated plates in a cold-flow pipe with a variable Mach number. These in-duct plates have the same porosities but different number N and geometric shaped orifices. Here six shapes are considered, i.e., (1) triangle, (2) square, (3) pentagon, (4) hexagon, (5) star, and (6) circle. It is shown that the orifice shape has little influence on power absorption Δ and reflection coefficient R at a lower Helmholtz number He ≤ 0.0903. However, as He is increased, the in-duct plate with a star-shaped orifice is shown to be with much lower Δ in comparison with that of other plates with different shape orifices. In addition, the perforated orifice with the same shape and porosity but a larger N is shown to be associated with 20% more power absorption at approximately He = 0.1244. Δmax is observed to be approximately 85% at about He = 0.0244, as Ma≈0.029. To gain more insights, the quasi-steady model is applied, depending on the Strouhal number Sr. The transition from quasi-steady flow behaviors to unsteady behaviors occurs at approximately Sr = 0.45. The measured minimum reflection coefficient Rmin occurs at Ma ≈ 0.024. This experimental finding is consistent with the quasi-steady prediction.